Pengaruh Sistem Zonasi dan Kurikulum Merdeka Terhadap Prestasi Siswa Dalam Pembelajaran Pendidikan Agama Islam Di SMAN 4 Pasuruan - Alfiyah, Nur (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2026)
Currently, the world of education is undergoing a significant transformation through the implementation of the zoning system and the Merdeka Curriculum. The zoning system aims to create equal access to education for all students. On the other hand, the Merdeka Curriculum is designed to provide a more flexible learning environment, while integrating character values through the Project to Strengthen the Profile of Pancasila Students (P5).This study aims to analyze the extent to which the zoning system and the Merdeka Curriculum influence students' academic achievement in Islamic Religious Education subjects.This study employs a correlational quantitative research design using a survey method. Correlational quantitative research is a type of study aimed at determining whether or not there is an influence between the variables being examined. Data collection techniques include observation, interviews, and documentation.The results of the study indicate that the zoning system has a positive and significant influence on student achievement, with a regression coefficient value of 0.837. Similarly, the Merdeka Curriculum also shows a positive and significant effect on student achievement, with a regression coefficient of 0.907.